Assessment of deformation processes in backfill masses using crushed rock models - Tkachuk, Oleksandr; Chepiga, Daria; Bachurin, Leonid; Podkopaiev, Serhii; Bachurina, Yaroslava; Podkopayev, Yevgen; Rudynets, Mykola; Visyn, Olena (Technology audit and production reserves, 2025)
The object of the study was the deformation processes in backfill masses made of crushed rock, which are used for roof control in mining panels. The study addressed the issue of preventing sidewall collapses by ensuring the stability of the backfill masses. Deformation processes were investigated using experimental models made of crushed rock that simulated various backfill structures. The study considered uniaxial compression of crushed rock with lateral expansion capability, as well as compressive loading. Uniaxial compression was used to simulate partial backfilling of the gob area, while compressive loading represented complete backfilling. Under loading conditions, a hyperbolic relationship was established between the relative volume change of the backfill material per unit of side rock convergence, ΔVK (m–1), and the compaction coefficient of crushed rock. This relationship enables the prediction of the material’s ultimate settlement. The determining factor in this relationship is the relative deformation of the backfill mass. Under loading of crushed rock and comparable compaction coefficient values, the difference in deformation properties reaches 2.5 to 3 times. This is recorded due to the transformation of shape or change in volume under different compression conditions. It is shown that with an increase in the parameter ΔVK, the specific potential energy of deformation of the backfill material changes according to a logarithmic relationship. The specific potential energy of deformation is determined by the mechanical properties and compression conditions of the crushed rock. Maximum stability of gob-side retained entries can be ensured through complete backfilling of the gob area, while the expected subsidence of the backfill mass depends on the initial backfill density and the deformation properties of the crushed rock used for filling.